Use of LARA-urea Breath Test in diagnosis of Helicobacter pylori Infection in Children and Adolescents: A Preliminary Study - Andrew S Day; Sander Veldhuyzen van Zanten; Anthony R Otley; Linda Best; AnneMarie Griffiths; Philip M Sherman (Canadian Journal of Gastroenterology)
BACKGROUND: An accurate diagnosis of Helicobacter pylori infection in children currently relies upon histological assessment or culture of gastric biopsies obtained at endoscopy. Noninvasive testing would permit simpler assessment of children with dyspeptic symptoms. The primary aim of the present study was to prospectively evaluate a novel urea breath testing method in children undergoing diagnostic assessment of dyspeptic symptoms and secondarily to consider the roles of other noninvasive tests in these children.